2010
DOI: 10.3390/s101110040
|View full text |Cite
|
Sign up to set email alerts
|

Non-Destructive Optical Monitoring of Grape Maturation by Proximal Sensing

Abstract: A new, commercial, fluorescence-based optical sensor for plant constituent assessment was recently introduced. This sensor, called the Multiplex® (FORCE-A, Orsay, France), was used to monitor grape maturation by specifically monitoring anthocyanin accumulation. We derived the empirical anthocyanin content calibration curves for Champagne red grape cultivars, and we also propose a general model for the influence of the proportion of red berries, skin anthocyanin content and berry size on Multiplex® indices. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
185
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(200 citation statements)
references
References 34 publications
12
185
1
2
Order By: Relevance
“…Those had a quite good correlation of 0.699 and 0.674, respectively [12]. Moreover, previous researchers also succeeded in promoting the chlorophyll fluorescence technique as a non-destructive evaluation for flavonols and anthocyanins in grapes [13].…”
Section: Potential Maturity Indices In Satsuma Mandarinmentioning
confidence: 87%
“…Those had a quite good correlation of 0.699 and 0.674, respectively [12]. Moreover, previous researchers also succeeded in promoting the chlorophyll fluorescence technique as a non-destructive evaluation for flavonols and anthocyanins in grapes [13].…”
Section: Potential Maturity Indices In Satsuma Mandarinmentioning
confidence: 87%
“…Three detectors are measuring the emitted fluorescence at the wavelengths of blue, red and far-red light. Ghozlen et al [46] and Cerovic et al [47] provide a more detailed description of the sensor. Table 2 gives an overview of the different ratios measured by the Multiplex R sensor.…”
Section: Multiplexmentioning
confidence: 99%
“…The fluorometer measurements resulted in a suite of indices from various combinations of the activation and detection wavelengths used (e.g. Ghozlen et al 2010), as shown in Table 2. Measurements were made to target the heads and top of the wheat canopy.…”
Section: Active Light Fluorometermentioning
confidence: 99%
“…A strong correlation (r = -0.87) was found between Fv/Fm measurements made immediately after exposure to À128C, and visual scoring of frost damage in the field for the corresponding cultivars tested. Wu et al (2012) used a handheld active light fluorometer to measure a nitrogen balance index (NBI_G; Ghozlen et al 2010) for potted wheat seedlings exposed to freezing temperatures, and assessed by visual inspection of apparent damage. With accumulation of freezing events, the NBI_G values actually increased, rather that decreased as would be expected.…”
Section: Previous Researchmentioning
confidence: 99%